Evaluating cytotoxic effect of the extracted compounds from Ehretia asperula Zoll. & Mor stem on several cancer cell lines - Nguyet, Vu Thi; Dat, Nguyen Tien; Huong, Le Mai; Hong Ha, Tran Thi; Chuyen, Nguyen Hong; Hang, Nguyen Thi; Kim, Dang Dinh (Academia Journal of Biology, 2018)
This paper reports the cytotoxic effect on several cancer cell lines of the stem extracts and of some isolated compounds from Ehretia asperula. All the extracts exhibited cytotoxic effects on at least one cancer cell line. The n-hexane extract showed potent cytotoxic activity on Hep-G2, MCF-7 and HeLa cell lines with IC50 values of 28.3 g/ml, 14.42 g/ml and 18.59 g/ml, respectively, while the methanolic, ethyl acetate and water extracts exhibited toxicity towards MCF-7 cells with IC50 values of 16.45 g/ml, 13.4 g/ml and 39.78 g/ml, respectively. 06 compounds have been isolated from the ethyl acetate fraction of Ehretia asperula stem. Methyl caffeate has a strong cytotoxicity against Hep-G2, HeLa and MCF-7 cancer cell lines with IC50 values of 2.83 g/ml, 3.38 g/ml and 4.4 g/ml, respectively. Oresbiusin B was active against Hep-G2 with IC50 value of 9.89 g/ml. The other compounds including coniferaldehyde, 9′-methoxydehydrodiconiferyl alcohol and vanillic acid did not have any cytotoxic effect on the tested cancer cell lines. So, the obtained results have suggested possibility of using the potential Ehretia asperula extracts as health food for preventing and curing cancer diseases. Keywords: Ehretia asperula, methyl caffeate, oresbiusin B, Cancer cell lines. Citation: Vu Thi Nguyet, Nguyen Tien Đat, Le Mai Huong, Tran Thi Hong Ha, Nguyen Hong Chuyen, Nguyen Thi Hang4, Đang Đinh Kim, 2018. Evaluating cytotoxic effect of the extracted compounds from ehretia asperula zoll. & mor stem on several cancer cell lines.Tap chi Sinh hoc, 40(2): 145153. https://doi.org/10.15625/0866-7160/v40n2.12955. *Corresponding author: dangkim.iet@gmail.com